Neurocircuit function in eating disorders. Issue 5 (9th May 2013) - Friederich, Hans‐Christoph; Wu, Mudan; Simon, Joe J.; Herzog, Wolfgang
Abstract Objective: Eating disorders are serious psychosomatic disorders with high morbidity and lifetime mortality. Inadequate response to current therapeutic interventions constitutes a challenging clinical problem. A better understanding of the underlying neurobiological mechanisms could improve psychotherapeutic and drug treatment strategies. Method: A review highlighting the current state of brain imaging in eating disorders related to the anxiety and pathological fear learning model of anorexia nervosa (AN) and the impulsivity model of binge eating in bulimia nervosa (BN). Results: Available neuroimaging studies in patients with acute AN primarily suggest a hyper‐responsive emotional and fear network to food, but not necessarily to eating disorder‐unrelated, salient stimuli. Furthermore, patients with AN show decreased activation in the ventral fronto‐striatal circuits during the performance of a cognitive flexibility task. Results in patients with BN primarily suggest a hypo‐responsive reward system to food stimuli, especially to taste reward. Additionally, patients with BN exhibit impaired brain activation in the inhibitory control network during the performance of general response–inhibition tasks. Discussion: Anxiety and pathological fear learning may lead to conditioned neural stimulus‐response patterns to food stimuli and increased cognitive rigidity, which could account for the phobic avoidance of food intake in patients with acute AN. However, further neurobiological studies are required to investigate pathological fear learning in patients with AN. Patients with BN may binge eat to compensate for a hypo‐responsive reward system. The impaired brain activation in the inhibitory control network may facilitate the loss of control over food intake in patients with BN. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:425–432)